Impact of Domestic Violence upon Mental Health of Secondary level School Girls - Mandal, Anil Kumar (Shanti Journal, 2022)
Abusing physically, mentally, sexually and economically by a person to a person who have familial relationship is domestic violence. This paper aims to describe what the relationship between impact of DV committed by mother and father, and mental health of girl students is. The study followed cross sectional research design and cluster sampling technique. Data of 385 students that were collected through self-administered anonymous questionnaire were analyzed. Descriptive and inferential statistics were applied. Pearson’s Correlation test was applied to identify what the relationship of abusing and beating have with anxiety and depression, and multiple regression analysis was used to predict significant contributor to DV. The great majority (84.6%) and 73.1% respondents who had experience of DV respectively had mild to moderate anxiety and depression. One in seven (15.4%) and 26.7% respondents respectively had severe anxiety and depression. Severity and frequency of abusing and beating had strong positive significant relationship with anxiety and depression. Severity and frequency of father beating contribute more to anxiety and depression. Local government must conduct domestic violence education for mothers and fathers of the study area.